Features of the country image’s formation as a priority direction of state policy (Herald of Journalism, 2018)
The formation of a favorable image of the country is a state strategic task. The country’s image isa mirror reflection of economic and cultural prosperity, an indicator of the effectiveness of the state’sindicator of the effectiveness of internal and external policy of the state. Promotes the strengthening ofinternational relations, it serves as an indicator of the state’s competitiveness in the global arena. Therole of mass media in the spiritual life of society is unconditional. The media are not only a means ofconveying information, but also form public opinion and the worldview of the individual. Besides, themass media play a certain role in the process of formation the country image. The media are not spreadthe information only, but also participate in the regulation of international relations. The article definesthe mass media as a strategic resource in the development of the country image. The role of Kazakhstanin world politics, the image of the country in solving international problems are determined. Also designatedPR-technologies in the development of the internal image of the country.Key words: country image, mass media, mass communication, international relations, foreign policy,UN.